Reflection of Al-Ghazali’s business ethics for tax consultants - Bima Rafly Fachrezzi; Deni Rachmad Sulistiyanto; Muhammed Lamin Jabbi; Ishiaka Adamu (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - The purpose of this study was to explore the application of the values of Al-Ghazali Islamic business ethics to tax consultants in Indonesia and to compare them with the Indonesian Tax Consultant Professional Code of Ethics.Method - This research approach uses phenomenology. There were 3 informants interviewed in the study consisting of tax consultants who are Muslim in Indonesia, fiscal authorities who are Muslim in Indonesia, and experts in the Islamic religion.Result - This research gives the result that the principle of integrity can be expanded in terms of its definition and meaning with the mujahadah component in Al-Mizan, so that the integrity referred to here is trying to keep away bad traits that are prohibited in Islam. Moreover, on the concept of al ihya', tax consultants have a main orientation to profit and the motivation to help taxpayers is still limited to improving the image of their consulting services business.Implication - The concept of Islamic Business Ethics by Al-Ghazali is a broader and deeper ethic so it is very appropriate if it is adapted to the Indonesian Tax Consultant Code of Ethics, especially regarding responsibility and motivation as servants of God.Originality - This research is the first study that used a phenomenological approach in uncovering the reflection of the concept of Islamic business ethics by Al-Ghazali on the implementation of a tax consultant's code of ethics.